2020
DOI: 10.1002/app.49975
|View full text |Cite
|
Sign up to set email alerts
|

Water‐born 3D nanofiber mats using cost‐effective centrifugal spinning: comparison with electrospinning process: A complex study

Abstract: A comparison of the electrostatic and centrifugal spinning of poly(vinyl alcohol) and poly(vinyl pyrrolidone) is shown in terms of the resulting fiber morphology and the process conditions. Specific parameters of centrifugal spinning, such rotational speed of spinneret and the relative humidity, were extensively investigated in details. Morphologies and diameters of resulting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…At high viscosity, centrifugal spinning led to fiber formation whereas electrospinning did not. In addition, spinning solutions were completely used in centrifugal spinning whereas 20-30% of the spinning solution was wasted in electrospinning [22]. Centrifugal spun nanofiber provides a 3 D porous structure which is advantageous in various nanofiber applications compared to electrospinning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high viscosity, centrifugal spinning led to fiber formation whereas electrospinning did not. In addition, spinning solutions were completely used in centrifugal spinning whereas 20-30% of the spinning solution was wasted in electrospinning [22]. Centrifugal spun nanofiber provides a 3 D porous structure which is advantageous in various nanofiber applications compared to electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of centrifugal spinning over electrospinning have been reported in nanofiber applications. Rihova et al [22] compared electrospun and centrifugally spun PVA and PVP nanofibers and found out that electrospinning yielded planar 2 D layers of fibers whereas centrifugal spinning yielded bulky 3 D structures. Moreover, the viscosity range of the studied polymers were broader with centrifugal spinning compared to that of electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the electrospinning process have expanded the range of the nanofiber assemblies from a 2D flat nanofiber mat to a 3D nanofibrous macrostructure [12][13][14][15]. With 3D nanofibrous scaffold fabricating techniques, including 3D template electrospinning, nanofiber film stacking, and centrifugal spinning [13][14][15][16], various 3D nanofibrous macrostructures have been fabricated, including a hollow tubular shape [17], molded 3D complex geometries [18], and native tissue-shaped nanofibrous scaffolds [19]. Such 3D nanofibrous macrostructures have become a growing topic of interest, particularly in tissue engineering, due to not only possessing a biomimetic nanofibrous structure but also mimicking a 3D macrostructure of native tissues [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrous materials are very intriguing structures with distinc-tive properties among other materials. They have a high porosity, a large specific surface area and good breathability [7]. For a wide variety of research and commercial utilization, nanofibres have appeared as a promising single-dimensional nanomaterial [8].…”
Section: Introductionmentioning
confidence: 99%